Coding-Based Energy Transformation Chain: Advancing Computational and Critical Thinking Skills Through Augmented Reality - Krisnadewi, Ni Kadek (Universitas Pendidikan Ganesha, 2024)
Critical reasoning and computational thinking skills among elementary school students remain low, particularly in understanding the concept of energy transfer between living organisms. This study aims to develop coding-based Augmented Reality (AR) learning media, the Energy Transformation Chain, which is valid, practical, and effective in improving these skills. The research adopts the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation). Data collection utilized essay test instruments and expert validation for media and material. Practicality data were gathered through student responses, while effectiveness was evaluated using a pre-experimental method with a one-group pretest-posttest design. The findings reveal that: the developed media exhibited high validity with an average score of 0.95 for media and 0.94 for materials, qualifying it as highly appropriate; the media was rated highly practical, achieving 93% in student responses; and the correlated t-test indicated a significance value (2-tailed) of 0.001 (p < 0.05), confirming the media's effectiveness in enhancing students' critical reasoning and computational thinking skills. In conclusion, the coding-based Augmented Reality learning media for the Energy Transformation Chain is valid, practical, and effective for educational use, making it a sustainable innovation to support students' skill development.